Pengaruh Fashion Involvement dan Positive Emotion Terhadap Impulse Buying di Centro Departemen Store Surabaya - Donie Rinto (Tourism Retailing+, 2013)
The purpise of this research is to identify impact of fashion involvement toward positive emotion and impulse buying, also the impact of positive emotion toward impulse buying. Research object is Cenntro Department Store Surabaya which the leading fashion in Surabaya. Variables used are: fashion involvement, positive emotion, and impulse buying. Research design is causal with 150 samples. Technique analysis of data used Structural Equation Model. The result of this research showing that fashion involvement proved impact toward positive emotion. Fashion involvement  proved impact towards impulse buying, but positive emotion not proved impact towards impulse buying.